The city school resource pack social studies class 1 (The City School Lahore, 2011)
The City School resource pack for social studies offers a comprehensive collection of materials designed to enhance students' understanding of their community, culture, and the world. It includes lesson plans, activities, and resources that encourage critical thinking about social issues, geography, history, and citizenship. The pack aims to foster engagement and discussion among students, helping them connect with their environment and develop a sense of responsibility towards their community.